A multi-omic analysis reveals a predictive value of tertiary lymphoid structures in improving the prognosis of colorectal cancer patients with BRAF mutation - Qin, Chao; Cheng, Shumin; Ma, Jingyun; Li, Lujing; Leng, Yun; Zheng, Lei; Chen, Huiying; Mo, Hui; Li, Shi; Liang, Yuhong; Zhang, Yi; Li, Wenxia; et al. (Frontiers in Immunology, 2025)
BackgroundBRAF mutations are prevalent in colorectal cancer (CRC) and generally confer a poor prognosis. Tertiary lymphoid structures (TLS), a critical component of the tumor immune microenvironment, exist in various malignancies and often correlate with improved immunotherapy response and survival. However, whether TLS can counteract the adverse prognostic effects of BRAF mutations in CRC remains unexplored. This study characterizes TLS features (location, number, maturity) as well as correlation to the BRAF mutation status and clinicopathological characteristics in CRC, and specifically evaluates the potential role of TLS in mitigating the negative prognostic impact of BRAF mutations.MethodsSingle-cell RNA sequencing data from GSE146771, GSE146771, GSE200997, GSE205506, and GSE231559, along with bulk RNA-seq data from the TCGA CRC cohort, were analyzed. Prognostic genes were identified using univariate Cox regression and least absolute shrinkage and selection operator (LASSO) regression, and subsequently used to construct TLS-related prognostic signatures. Kaplan-Meier survival analysis and receiver operating characteristic (ROC) curve analysis were used to evaluate the predictive performance of the signature. Immune infiltration was assessed using the ESTIMATE and CIBERSORT algorithms. Histopathological evaluation of TLS was conducted in tissue sections from 200 CRC patients. Clinicopathological features were compared between the BRAF wild-type (BRAFWT) and BRAF mutant (BRAFMT) groups. Associations between BRAF mutation status and TLS location, number, maturity, as well as overall survival (OS), were analyzed.ResultsTLS displayed distinct expression patterns within the CRC tumor microenvironment. A 10-gene prognostic model was developed based on LASSO regression analysis. Patients with BRAFMT CRC exhibited unfavorable clinicopathological characteristics, including poor differentiation, advanced T stage, and lymph node metastasis. Meanwhile, BRAFWT CRC was associated with a greater number and higher maturity of TLS. Notably, patients with BRAFWT, TLS-high (TLSHigh), and BRAFWT-TLSHigh subgroups showed significantly improved OS compared to other groups.ConclusionTLS-related prognostic signatures serve as effective tools for predicting CRC outcomes. Moreover, intratumorally TLS may enhance the prognosis of patients with BRAFMT CRC, highlighting its potential as a therapeutic and prognostic biomarker. Colorectal cancer, BRAF mutation, tertiary lymphoid structures, tumor microenvironment, prognosis.